2011
DOI: 10.1179/026708310x520510
|View full text |Cite
|
Sign up to set email alerts
|

Solid state joining of metals by linear friction welding: A literature review

Abstract: Linear friction welding (LFW) is a solid state joining process in which a joint between two metals can be formed through the intimate contact of a plasticised layer at the interface of the adjoining specimens. This plasticised layer is created through a combination of frictional heating, which occurs as a result of pushing a stationary workpiece against one that is moving in a linear reciprocating manner, and applied force. The process is currently established as a niche technology for the fabrication of titan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 30 publications
1
78
0
3
Order By: Relevance
“…[2,4,8,11,13] The different zones are displayed in Figure 5(a). The WCZ which many authors suggest experiences significant recrystallization, [4,8,11,13] was found to have either a widmanstatten and/or martensitic microstructure, as shown in Figures 5(b) and (c), respectively. The WCZ was then followed by a TMAZ.…”
Section: A Weld Appearance and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…[2,4,8,11,13] The different zones are displayed in Figure 5(a). The WCZ which many authors suggest experiences significant recrystallization, [4,8,11,13] was found to have either a widmanstatten and/or martensitic microstructure, as shown in Figures 5(b) and (c), respectively. The WCZ was then followed by a TMAZ.…”
Section: A Weld Appearance and Microstructurementioning
confidence: 99%
“…[4,8,11,12] Computational models are particularly useful as they provide a means of predicting what happens at the weld interface in the rapidly evolving process. However, the models are limited by a lack of data [13] -in particular, the interface force, friction coefficient, and steady-state burn-off rate as a function of the process inputs for the different phases of a weld. This paper addresses these issues using a systematic design of experiments to determine the effects of the process inputs on the average values of these outputs for the different phases of the process for Ti6Al-4V linear friction welds.…”
Section: Linear Friction Welding (Lfw) Is a Solid-statementioning
confidence: 99%
“…Furthermore, it should be noted that this work studies the reproducibility of the welds, hence, the analysis of the influence of the different phases on the weld is not a part of this study. The interested reader is referred to the papers by Vairis and Frost [5] and Bhamji et al [3], where the influence of the weld phases on the parameters is discussed in much greater detail. However, the methodology presented here can be easily extended to do such a mechanistic analysis of the weld parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The friction generates heat, which is enough to make the material ductile. In the first instance the rubbing is used to remove the outer layer of material, this is called burn-off in this work and comprises what is generally known as the initial (conditioning, [3]), the transition and equilibrium (frictional, [3]) and the first part of the deceleration (forge, [3]) phases [5], see Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation